FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI MENANAM JAGUNG MANIS DAN JAGUNG LOKAL - David Harksel Andre Ratulangi; Theodora Maulina Katiandagho; Benny Adrian Berthy Sagay (Sam Ratulangi University, 2019)
This study aims to determine the factors that influence farmers' decisions in planting sweet corn and local corn in Tolombukan Satu Village, Pasan District, Southeast Minahasa Regency. Data collection was carried out for two months, from May to June 2019. The collected data was compiled quantitatively and displayed in tabular form. This research uses primary data and secondary data. Primary data obtained from interviews and with the help of questionnaires for the leader (chair, secretary, and treasurer) and all members of the Nafiri Jaya Farmer Group amounted to 20 people. Secondary data obtained from local book store, the internet through Google Scholar to get articles and theses from other universities related to research topics on factors that influence farmers' decisions. The results showed that the factors influencing the decision of farmers to plant sweet corn and local corn were social factors and economic factors. Social factors consist of age, level of education, experience in farming and the role of agricultural extension workers. Economic factors consist of the number of dependents in the family, land area, facilities and infrastructure, income, expenses and selling price.*eprm*